analisis kesalahan siswa dalam menyelesaikam soal cerita sistem persamaan linear dua variabel menggunakan fase newman - Sonya Grace Eveline Sianipar (Program Studi S1 Matematika UNESA, 2020)
In learning mathematics, students often make mistakes in solving math questions, especially story questions. Solving story questions, students are required to understand the contents of the story questions and take them in the form of mathematical symbols and process them using mathematical methods until the final stage and draw conclusions. The aim of the research is to describe locations, types, and causes of VIII grade Students’ errors in solving story questions of Two-variable Linear Equality System using Newmann’s Error Analysis. Newman’s Error Analysis namely Reading error, comprehension error, transformation error, process skill error, and an encoding error. The result of this research says the students made many mistakes in reading the story question, transforming into a mathematic model onto the encoding stage. The types of errors that were made were: students were wrong concepts, there including wrong in modeling and students were wrong in operations, i.e. students did not use the right arithmetic operation. The cause of the errors is that the subject is bad in the concept of the variable, including being unable to read the symbols implied in the problem. Unable to transform question to math-model correctly, weak in making equivalent questions, and weak in determining calculation result rightly. Keywords: Error Analysis, Newmann, Two-variables Linear Equality System, and Story Question.